SURVEI KEAKTIFAN SISWA DALAM KEGIATAN GIZI BOKS (BUILD OUR KIDS SUCCESS’) PADA MATA PELAJARAN PJOK DI KELAS RENDAH SEKOLAH DASAR - Safira Atmojo, Rachmadania; Linda Zakiah; M. Syarif Sumantri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Physical Education, Sports, and Health have a very important role to make us strong and skilledhuman beings. This study shows that education is not only about academics, but also preparesindividuals to face life's challenges. PJOK provides more than just physical health, it also develops social, emotional, and moral aspects. The BOKS program is an initiative to improve children's welfare through physical activities and nutrition education at the elementary school level. The purpose of this study was to measure the extent of student activity in BOKS Nutrition activities in PJOK subjects in elementary school lower grades. Researchers use quantitative research methods of survey type with instruments in the form of questionnaires. The population in this study was all low-grade students in elementary school with a total of 100 students. The results of this study obtained the level of student activeness with an average percentage of 64% included in the very good majority category which reflects the high involvement of students in learning. This confirms the importance of innovation in PJOK learning, including the use of interesting and effective methods, as well as continuous evaluation of their impact on the quality of learning and student activity.